Operative Dictations in Plastic and Reconstructive Surgery - Anh Tran, Tuan.; Panthaki, Zubin J.; Hoballah, Jamal J.; Thaller, Seth R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text provides a comprehensive overview of operative dictations in plastic, aesthetic, and reconstructive surgical procedures, which will serve as a valuable resource for residents, fellows, and practicing surgeons. The book provides step-by-step operative details regarding all indexed plastic surgery cases that a resident is expected to be thoroughly acquainted with for his or her daily practice and examinations. Each case is preceded by a list of common indications, covering most of the situations in which particular procedures will be used, as well as a list of essential steps. Operative Dictations in Plastic and Reconstructive Surgery will serve as a very useful resource for physicians dealing with, and interested in the field of plastic surgery. It will also provide the related data for the newly minted practicing plastic surgeons. All chapters are written by authorities in their fields and include the most up-to-date scientific and clinical information. .
Skin Graft -- Scar Revision with Z-plasty -- Botulinum Toxin (BoNT-A) Denervation -- Dermal Fillers Injection -- Facial Skin Resurfacing -- Brow Lift -- Blepharoplasty -- Facelift -- Structural Fat Grafting of the Face -- Skeletal Augmentation -- Rhinoplasty -- Otoplasty -- Hair Restoration -- Liposuction -- Abdominoplasty -- Belt Lipectomy -- Lower Body Lifts -- Medial Thigh Lift -- Buttock Augmentation -- Brachioplasty -- Aesthetic Gential Surgery -- Open Reduction and Internal fixation of Orbital Floor Fracture -- Open Reduction and Internal Fixation of Zygomaticomaxillary Complex Fracture -- Zygomatic Arch Fracture Reduction -- Transnasal Wiring of Nasoorbitoethmoid Fracture -- Closed/Open Nasal Reduction -- Scalp/Calvarial Reconstruction -- Eyelid Recontruction -- Nasal Reconstruction -- Reconstruction of the Ear -- Facial Paralysis -- Cheek Reconstruction -- Repair of Lip Defect -- Mandibular Reconstruction -- Neck Reconstruction -- Correction of Facial Countour Deformities with Free Parascapular Flap -- Orthognathic Surgery -- Cleft Lip Repair -- Cleft Palate -- Velopharyngeal Insufficiency -- Microtia Repair -- Reconstruction of Congential Urogential Defects -- Lymphatic Reconstruction of the Lower Extremities -- Lower Extremity Reconstruction -- Foot Reconstruction -- Reconstruction of the Chest -- Reconstruction of the Soft Tissues of the Back -- Spinal Closure -- Abdominal Wall Reconstruction -- Pressure Sore -- Reconstruction of Male Genital Defects -- Reconstruction of Acquired Vaginal Defects -- Surgery for Gender Identity Disorder -- Perineal Reconstruction -- Burn -- Breast Augmentation -- Mastopexy -- Reduction Mammoplasty -- Breast Reconstruction -- Reconstruction of the Nipple-Areola Complex -- Fat Grafting to the Breast -- Gynecomastia -- Nail and Fingertip Reconstruction -- Open TFCC Repair -- Extensor Retinaculum Capsulorrhapy -- Treatment of Distal Radius Fracture -- Treatment of Scaphoid Fracture -- Proximal Row Carpectomy -- Four Corners Fusion -- Total Wrist Arthrodesis -- Treatment of Metacarpal and Phalangeal Fracture -- Reconstruction of Flexor Tendon Injury -- Repair of Central Tendon Slip with Mitek Anchor Suture -- Tendon Graft -- Replantation -- Revascularization -- Congential -- Thumb Reconstruction -- Thumb and Finger Reconstruction: Microsurgical Techniques -- Soft Tissue Coverage of the Hand -- Hand Infection -- Benign Tumor -- Dupuytren's Disease -- Rheumatoid Arthritis Hand -- Osteoarthritis Hand -- Compartment Syndrome -- Compression Syndrome -- Trigger Finger Release -- Trigger Thumb Release -- Nerve Repair -- Nerve Transfer -- Tendon Transfer.
Keywords: Medicine; Rectum -- Surgery; Surgery; Plastic surgery; Vascular surgery; Medicine & Public Health; Plastic surgery; Vascular surgery; General Surgery; Colorectal Surgery